Whatever Happened to ISDN? - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2025)
In the 90th year of publication of this, our local journal, it is fitting to look back at some technologies or services that were once popular topics but whose time has now passed. This paper looks at the history of the Integrated Services Digital Network (ISDN) as it is reflected in the pages of the Telecommunication Journal of Australia (TJA). ISDN was popular in the 1980s: in the period 1984–1990, no less than 15 papers were published in the TJA, about 6% of the papers in those years. ISDN quickly disappeared from publications with the rise of the Internet and ADSL in the 1990s. The accompanying historical reprint from 1986 describes the transmission issues associated with providing ISDN customer access and presents some of the design decisions made by Telecom Australia.